Ferritic Stainless Steel Wire
By controlling the radial crystal orientation and reducing the intensity ratio of the NbLaves phase in ferritic stainless steel wires, the issue of cracks during screw rolling is addressed, resulting in improved crack resistance and enhanced performance in cold forging applications.
Patent Information
- Application Number
- JP2021037647
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-09
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-09
AI Technical Summary
Existing ferritic stainless steel wires containing Nb suffer from cracks during screw rolling due to the precipitation of the NbLaves phase, which reduces toughness and plastic deformation ability, and current technologies fail to adequately control the NbLaves phase or crystal orientation to enhance crack resistance.
A ferritic stainless steel wire with a specific chemical composition and controlled crystal orientation, where the radial crystal orientation ND// fraction is 0.1 or higher, and the intensity ratio of the NbLaves phase is 0.3 or less, is developed to improve crack resistance.
The proposed solution effectively enhances the crack resistance of ferritic stainless steel wires, achieving a cracking rate of 80% or less, thereby improving the wires' durability and performance in cold forging applications.
Smart Images

Figure 0007670507000001 
Figure 0007670507000002 
Figure 0007670507000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel wire. [Background technology]
[0002] Conventionally, high purity ferritic stainless steel wire containing Nb has been used for cold forging parts. However, during thread rolling, fray cracks, which are brittle fractures, can occur. The reason for this is that in high purity ferritic stainless steel wire containing Nb, the Fe2Nb Laves phase precipitates in the steel structure, reducing toughness, and the number of {110} planes, which are slip planes, decreases on the ND plane in the fray crack direction, reducing plastic deformability. Fray cracks are longitudinal cracks that occur when compressive stress is applied in the radial direction by rolling.
[0003] Patent Documents 1 to 4 disclose steels in which the Fe2Nb Laves phase or crystal orientation is appropriately controlled to improve toughness. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 196595 [Patent Document 2] International Publication No. 2015 / 147211 [Patent Document 3] JP 2005-139509 A [Patent Document 4] Re-tabled publication No. 2017-135240 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there has been no technology to date that has investigated the improvement of bending crack resistance by controlling the Fe2NbLaves phase or crystal orientation. In addition, there is no technology that simultaneously controls the Fe2NbLaves phase and the crystal orientation, and the bending crack resistance cannot be sufficiently ensured with conventional technology. In light of the above, an object of the present invention is to solve the above problems and provide a ferritic stainless steel wire that is excellent in bending crack resistance. [Means for solving the problem]
[0006] The present invention has been made to solve the above problems, and the gist of the present invention is the following steel wire. (1) In mass percent, C: 0.001-0.08%, Si: 0.01 to 3.0%, Mn: 0.01 to 2.0%, P: 0.20% or less, S: 0.050% or less, Ni: 0.01-4.0%, Cr: 8.0~30.0%, Mo: 0.01-4.0%, Cu: 0.01-3.0%, N: 0.001 to 0.10% and Nb: 0.2 to 2.0% The steel has a composition including the remainder Fe and impurities, Radial crystal orientation ND / / <110> A ferritic stainless steel wire having a Nb2CN fraction of 0.1 or more and an intensity ratio of the maximum peak of the Fe2Nb Laves phase (2θ = approximately 44°) to the maximum peak of the Nb2CN (2θ = approximately 35°) as determined by XRD analysis of 0.3 or less. However, the radial crystal orientation ND / / <110> What is a fraction? <110> It means the area ratio of crystals whose angle difference between the orientation and the radial direction is 20° or less.
[0007] (2) The steel composition contains, in mass%, Fe, in place of a portion of the Fe, Ti: 2.0% or less, V: 2.0% or less, B: 0.1% or less, Al: 4.0% or less, W: 2.5% or less, Ga: 0.05% or less, Co: 2.0% or less, Sn: 2.0% or less and The ferritic stainless steel wire according to (1) above, characterized in that it contains one or more elements selected from the group consisting of Ta: 2.0% or less. (3) The steel composition contains, in mass%, replacing a part of the Fe, Ca: 0.05% or less, Mg: 0.012% or less, Zr: 0.012% or less and The ferritic stainless steel wire according to (1) or (2) above, characterized in that it contains one or more selected from the group consisting of REM: 0.05% or less.
[0008] (4) The ferritic stainless steel wire according to any one of (1) to (3), having a crack occurrence rate of 80% or less. (5) The ferritic stainless steel wire according to any one of (1) to (3), wherein the cross-sectional shape of the steel wire is a circle, and the diameter of the circle is 2 to 10 mm. Effect of the Invention
[0009] According to the present invention, a steel wire having excellent resistance to bending cracks can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present inventors have conducted various investigations in order to obtain a steel wire having excellent resistance to bending cracking, and as a result, have obtained the following findings (a) to (d).
[0011] (a) ND / / in metal structure <110> By controlling the fraction to be high, the resistance to bending cracking of the steel wire is improved.
[0012] (b) By controlling the amount of precipitation of the Fe2Nb Laves phase to be small, the resistance to bending cracking of the steel wire is improved.
[0013] (c) The Fe2NbLaves phase is easily precipitated on the {110} plane, which is the slip plane. Therefore, by simultaneously achieving (a) and (b), the proportion of the Fe2NbLaves phase on the {110} plane is further reduced. This effect makes it easier to undergo slip deformation, resulting in a greater improvement in resistance to chipping than the simple addition of the effects of (a) and (b).
[0014] (d) The above mentioned ND / / <110> In order to control the fraction and amount of Fe2Nb Laves phase precipitation, it is desirable to adjust the chemical composition, manufacturing conditions, specifically, the wire drawing rate, the heating rate during finish annealing, temperature, holding time, cooling rate, skin pass processing rate, etc. In particular, it is important to control the cold drawing rate and the cooling rate during finish annealing.
[0015] The present invention has been made based on the above findings. A preferred embodiment of the present invention will be described in detail. In the following description, a preferred embodiment of the present invention will be described as the present invention. Each of the requirements of the present invention will be described in detail below.
[0016] In the steel wire according to the present invention, the crystal orientation in the radial direction (ND) is controlled. Specifically, the crystal orientation in the radial direction ND / / <110> Fraction (area ratio) (hereinafter simply "ND / / <110> It is preferable that the ND / / fraction is 0.1 or more. <110> If the fraction is less than 0.1, slip deformation is suppressed, brittle fracture is promoted, and resistance to flex cracking decreases. <110> The fraction is more preferably 0.15 or more, and even more preferably 0.2 or more.
[0017] In addition, ND / / <110> The fraction is calculated using the following procedure: ND / / <110> The fraction is calculated by measuring an area of 500 μm x 500 μm or more in one or more visual fields in the surface layer, center, and 1 / 4 depth position between the surface layer and center in the L cross section of the steel wire (a cross section parallel to the longitudinal direction of the steel wire and passing through the center line of the steel wire), and using the following formula. The crystal orientation of each crystal grain is analyzed using FE-SEM / EBSD. The radial direction is defined as ND, and the crystal orientation in the ND direction is analyzed. <110> Display only the azimuth components within a clearance of 20°, and ND / / <110> The surface layer refers to a depth of 0.5 mm from the surface toward the center. <110> What is a fraction? <110> It means the area ratio of crystals whose angle difference between the orientation and the radial direction is 20° or less. Crystal orientation ND / / <110> Fraction = (Fraction (surface layer) x 2 + Fraction (1 / 4 depth position) x 2 + Fraction (center)) / 5
[0018] In the steel wire according to the present invention, the amount of precipitation of the Fe2Nb Laves phase is controlled. Specifically, the intensity ratio of the maximum peak (2θ=about 44°) of the Fe2Nb Laves phase to the maximum peak (2θ=about 35°) of Nb2CN by XRD analysis (hereinafter simply referred to as the "intensity ratio of the Fe2Nb Laves phase to Nb2CN") is preferably 0.3 or less. If the intensity ratio of the Fe2Nb Laves phase to Nb2CN exceeds 0.3, brittle fracture is promoted and the resistance to chirping cracks is reduced. The intensity ratio of the Fe2Nb Laves phase to Nb2CN is more preferably 0.2 or less, and even more preferably 0.15 or less.
[0019] The intensity ratio of the Fe2NbLaves phase to Nb2CN is calculated using the following procedure. The precipitates collected from the extraction residue were analyzed using XRD. In the diffraction chart, the maximum peak of Nb2CN is at 2θ = about 35°, and the maximum peak of the Fe2NbLaves phase is at 2θ = about 44°. The intensity of these peaks with the background removed was measured, and the intensity ratio of the Fe2NbLaves phase to Nb2CN was calculated.
[0020] The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0021] C increases the strength of the steel wire. For this reason, the C content is set to 0.001% or more, and preferably 0.002% or more. However, if C is contained excessively, ND / / <110> The carbon fraction decreases. As a result, the resistance to cracking decreases. Also, the corrosion resistance may decrease. For this reason, the carbon content is set to 0.08% or less. The carbon content is preferably set to 0.05% or less, more preferably set to 0.03% or less, and even more preferably set to 0.02% or less.
[0022] Silicon is contained as a deoxidizing element to improve high-temperature oxidation properties. For this reason, the silicon content is set to 0.01% or more, and preferably 0.05% or more. However, excessive silicon content results in ND / / <110> The Si content is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less.
[0023] Mn improves the strength of the steel wire. For this reason, the Mn content is set to 0.01% or more, and preferably 0.05% or more. However, if Mn is contained excessively, the ND / / <110> The Mn fraction decreases. As a result, the resistance to cracking decreases. Also, there are cases where the corrosion resistance decreases. For this reason, the Mn content is set to 2.0% or less. The Mn content is preferably set to 1.0% or less, more preferably set to 0.8% or less, and even more preferably set to 0.5% or less.
[0024] P and S are mixed in as impurities from the raw materials, but excessive content of these elements reduces corrosion resistance and significantly reduces manufacturability. For this reason, the content of each element is set to 0.20% or less for P and 0.050% or less for S. The P content is preferably set to 0.10% or less. The S content is preferably set to 0.030% or less.
[0025] Ni improves the resistance to bending cracking of steel wire. For this reason, the Ni content is set to 0.01% or more, and preferably 0.05% or more. However, excessive Ni content causes ND / / <110> The Ni content is preferably 2.0% or less, more preferably 1.0% or less, and even more preferably 0.5% or less.
[0026] Cr improves corrosion resistance. For this reason, the Cr content is set to 8.0% or more. The Cr content is preferably set to 10.0% or more, and more preferably set to 15.0% or more. However, excessive Cr content may cause ND / / <110> The Cr content is preferably 30.0% or less, more preferably 25.0% or less, and even more preferably 21.0% or less.
[0027] Mo improves corrosion resistance. For this reason, the Mo content is set to 0.01% or more. However, excessive Mo content causes ND / / <110> The Mo content is set to 4.0% or less. The Mo content is preferably set to 2.0% or less, more preferably set to 1.0% or less, and even more preferably set to 0.5% or less.
[0028] Cu improves corrosion resistance. For this reason, the Cu content is set to 0.01% or more, and preferably 0.30% or more. However, excessive Cu content causes ND / / <110> The Cu content is set to 3.0% or less. The Cu content is preferably set to 2.0% or less, more preferably set to 1.0% or less, and even more preferably set to 0.5% or less.
[0029] N improves the strength of the steel wire. For this reason, the N content is set to 0.001% or more, and preferably 0.004% or more. However, if N is contained excessively, ND / / <110> The N content is reduced. As a result, the resistance to cracking is reduced. For this reason, the N content is set to 0.10% or less. The N content is preferably set to 0.05% or less, more preferably set to 0.03% or less, and even more preferably set to 0.02% or less.
[0030] Nb forms carbonitrides, which suppresses the formation of Cr carbides and suppresses the formation of Cr depleted layers. As a result, Nb has the effect of preventing intergranular corrosion. That is, since Nb is an element that is effective in improving corrosion resistance, the Nb content is set to 0.2% or more, and preferably 0.3% or more. However, excessive Nb content promotes the precipitation of Fe2NbLaves phase, which reduces the resistance to rubbing cracking. In addition, the Nb carbonitrides become coarse, which reduces the resistance to rubbing cracking. For this reason, the Nb content is set to 2.0% or less. The Nb content is preferably set to 1.0% or less, and more preferably 0.8% or less.
[0031] The stainless steel of the present invention is composed of a chemical composition consisting of Fe and impurities other than the elements mentioned above. In addition to the above-mentioned composition, the following is selectively used in place of a part of Fe. The elements shown may be contained.
[0032] It is not necessary to add Ti. If added, it has the effect of increasing the strength of the steel wire. In addition, Ti forms carbonitrides, which suppresses the formation of Cr carbides and the formation of a Cr-deficient layer. As a result, Ti has the effect of preventing intergranular corrosion. However, if Ti is contained in excess, the ND / / <110> The Ti content is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.05% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably 0.001% or more.
[0033] V does not have to be added. If added, it has the effect of improving corrosion resistance. However, if V is contained in excess, ND / / <110> The fraction of V decreases. As a result, the resistance to martensitic cracking decreases. Furthermore, the resistance to martensitic cracking decreases due to coarse carbonitrides. For this reason, the V content is set to 2.0% or less. The V content is preferably set to 1.0% or less, more preferably set to 0.5% or less, and even more preferably set to 0.1% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.001% or more.
[0034] B does not have to be added. If added, it has the effect of improving hot workability and corrosion resistance. However, if B is contained in excess, ND / / <110> The B content is preferably 0.02% or less, and more preferably 0.01% or less. On the other hand, in order to obtain the above effect, the B content is preferably 0.0001% or more.
[0035] It is not necessary to add Al. If added, it promotes deoxidation and has the effect of improving the inclusion cleanliness level. However, if Al is contained in excess, the effect becomes saturated and ND / / <110> The Al fraction decreases. As a result, the resistance to cracking decreases. Furthermore, the resistance to cracking decreases due to coarse inclusions. For this reason, the Al content is set to 4.0% or less. The Al content is preferably set to 1.0% or less, more preferably set to 0.1% or less, and even more preferably set to 0.01% or less. On the other hand, in order to obtain the above effect, the Al content is preferably set to 0.001% or more.
[0036] W does not have to be added. If added, it has the effect of improving corrosion resistance. However, if W is contained in excess, ND / / <110> The fraction of W decreases. As a result, the resistance to martensitic cracking decreases. Furthermore, the resistance to martensitic cracking decreases due to coarse carbonitrides. For this reason, the W content is set to 2.5% or less. The W content is preferably set to 2.0% or less, and more preferably set to 1.5% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.05% or more, and more preferably set to 0.10% or more.
[0037] Ga does not have to be added. If added, it has the effect of improving corrosion resistance. However, if Ga is contained in excess, hot workability decreases. For this reason, the Ga content is set to 0.05% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.0004% or more.
[0038] Co does not have to be added. If added, it has the effect of improving the strength of the steel wire. However, if Co is contained in excess, the ND / / <110> The fraction of Co decreases. As a result, the resistance to cracking decreases. For this reason, the Co content is set to 2.0% or less. The Co content is preferably set to 1.0% or less, and more preferably set to 0.8% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.05% or more, and more preferably set to 0.10% or more.
[0039] Sn does not have to be added. If added, it has the effect of improving corrosion resistance. However, if Sn is added in excess, ND / / <110> The fraction of Sn decreases. As a result, the resistance to rubbing cracking decreases. Furthermore, the resistance to rubbing cracking decreases due to grain boundary segregation of Sn. For this reason, the Sn content is set to 2.0% or less. The Sn content is more preferably set to 1.0% or less, and even more preferably set to 0.2% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.01% or more, and more preferably set to 0.05% or more.
[0040] Ta does not have to be added. If it is added, it has the effect of improving corrosion resistance. However, if Ta is contained in excess, ND / / <110> The Ta content is preferably 1.5% or less, and more preferably 0.9% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably 0.01% or more, more preferably 0.04% or more, and even more preferably 0.08% or more.
[0041] Ca, Mg, Zr and REM do not have to be added. If added, they have a deoxidizing effect. However, if these elements are contained in excess, ND / / <110> The Ca content is preferably 0.010% or less, and more preferably 0.005% or less. The Mg content is preferably 0.010% or less, and more preferably 0.005% or less. The Zr content is preferably 0.010% or less, and more preferably 0.005% or less. The Zr content is preferably 0.010% or less, and more preferably 0.005% or less. The REM content is preferably 0.010% or less, and more preferably 0.005% or less. On the other hand, in order to obtain the above effects, it is preferable that Ca: 0.0002% or more, Mg: 0.0002% or more, Zr: 0.0002% or more, and REM: 0.0002% or more. The Ca content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The Mg content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The Zr content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The REM content is more preferably 0.0004% or more, and even more preferably 0.001% or more. REM is a collective term for 17 elements, including 15 lanthanoid elements, Y, and Sc. One or more of these 17 elements can be contained in steel, and the REM content refers to the total content of these elements.
[0042] In the chemical composition of the steel wire of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of the steel wire, and are permissible within a range that does not adversely affect the present invention.
[0043] Since the steel wire according to the present invention is produced by wiredrawing in the final manufacturing process, the cross-sectional shape perpendicular to the wiredrawing direction is circular. The diameter of the circle is preferably in the range of 2 to 10 mm. If the diameter of the circle is less than 2 mm, the rolling property deteriorates, so the diameter of the circle is preferably 2 mm or more, and more preferably 3 mm or more. However, if the diameter of the circle is more than 10 mm, ND / / <110> The fraction decreases. As a result, the resistance to cracking decreases. For this reason, the diameter of the circle is preferably 10 mm or less, more preferably 8 mm or less, and even more preferably 6 mm or less.
[0044] For the steel wire according to the present invention, the resistance to rice cracking was evaluated based on the crack occurrence rate in a drop weight test. This test method makes it possible to reproduce a crack form similar to rice cracking, and to evaluate the resistance to rice cracking with high accuracy. The test specimens were cylindrical, 15 mm long, and were made by cutting and machining the steel wire to make the cross section smooth. The test temperature was maintained at -196°C using liquid nitrogen. When the impact energy calculated by the following formula (1) was 20 J / cm 2 Under the above conditions, 10 or more test pieces were evaluated. Impact energy (J / cm 2 ) = mass of weight (kg) × acceleration of gravity (m / s 2 ) × Drop weight height (m) ÷ Cross-sectional area of test piece in wire drawing direction (cm 2 ) · · · (1) Cracks were judged by visual observation of the appearance after the test. The number of cracks relative to the number of test pieces was evaluated as the crack occurrence rate. If the crack occurrence rate is 80% or less, it is judged that the resistance to rubbing cracking is good. The resistance to rubbing cracking is preferably 70% or less, more preferably 60% or less, and even more preferably 50% or less. In addition, from the viewpoint of the components involved in crystal orientation control and precipitation control of the Fe2NbLaves phase, and the cost due to manufacturing constraints, the preferable lower limit of the crack occurrence rate is 5%.
[0045] A preferred method for producing the steel wire according to the present invention will be described. The steel wire according to the present invention can obtain the effects thereof as long as it has the above-mentioned configuration regardless of the production method, but the steel wire according to the present invention can be stably obtained, for example, by the following production method.
[0046] In the steel wire according to the present invention, a steel having the above-mentioned chemical composition is melted, a slab having a predetermined diameter is cast, and then hot or warm wire rolling is performed. After that, annealing is performed, and one or more cold drawing and annealing are repeated, followed by pickling and skin pass drawing to obtain a steel wire.
[0047] Cold drawing may be performed one or more times depending on the difference in diameter between the wire rod and the steel wire. When cold drawing is performed multiple times, intermediate annealing is usually performed between each cold drawing. However, it is preferable that the final cold drawing rate (the drawing rate of the cold drawing performed after the final intermediate annealing) is 20% or more. If the final cold drawing rate is less than 20%, ND / / <110> The fraction of the wire drawn is decreased. As a result, the resistance to bending cracking is decreased. Therefore, the final cold wire drawing ratio is set to 20% or more, more preferably 25% or more, and even more preferably 30% or more. The cold wire drawing ratio means the reduction in area caused by cold wire drawing.
[0048] The final annealing following the cold drawing may be performed once or more depending on the difference in diameter between the wire rod and the steel wire. However, the temperature rise rate during the final annealing is preferably 200° C. / min or less. If the temperature rise rate during the final annealing exceeds 200° C. / min, ND / / <110> As a result, the resistance to cracking decreases. Therefore, the heating rate during the finish annealing is set to 200° C. / min or less, more preferably 150° C. / min or less, and further preferably 100° C. / min or less.
[0049] The temperature during the final annealing is preferably in the range of 800 to 1100° C. The final annealing causes the Fe2NbLaves phase to dissolve, and the ND / / <110> The fraction of FeNb increases. As a result, the resistance to cracking is improved. If the temperature during the final annealing is less than 800°C, the Fe2NbLaves phase does not dissolve. As a result, the resistance to cracking is reduced. For this reason, the temperature during the final annealing is preferably 800°C or higher, and more preferably 850°C or higher. However, if the temperature during final annealing exceeds 1100°C, ND / / <110> As a result, the resistance to cracking is reduced. Therefore, the temperature during the finish annealing is preferably 1100°C or less, and more preferably 1000°C or less.
[0050] The holding time during final annealing is preferably in the range of 5 to 600 min. If the holding time during final annealing is less than 5 min, the Fe2NbLaves phase does not dissolve. As a result, the resistance to bending cracking is reduced. Therefore, the holding time during final annealing is preferably 5 min or more, and more preferably 30 min or more. However, if the holding time during final annealing is more than 600 min, ND / / <110> As a result, the resistance to cracking is reduced. Therefore, the holding time during the final annealing is preferably 600 min or less, and more preferably 500 min or less.
[0051] In addition, the cooling rate during the final annealing is preferably 0.5°C / min or more. If the cooling rate during the final annealing is less than 0.5°C / min, a large amount of the dissolved Fe2NbLaves phase precipitates. As a result, the resistance to cracking decreases. For this reason, the cooling rate during the final annealing is preferably 0.5°C / min or more, and more preferably 2°C / min or more.
[0052] The skin pass drawing rate is preferably in the range of 1 to 20%. If the skin pass drawing rate is less than 1%, ND / / <110> As a result, the resistance to bending cracking decreases. Therefore, the skin pass wire drawing rate is preferably set to 1% or more, and more preferably set to 2% or more. However, when the skin pass drawing rate is more than 20%, ND / / <110> As the fraction decreases, work hardening occurs. As a result, the resistance to bending cracking decreases. For this reason, the skin-pass wire drawing rate is preferably 20% or less, and more preferably 15% or less. The skin-pass wire drawing rate refers to the reduction in area caused by skin-pass wire drawing.
[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0054] Steels having the chemical compositions shown in Tables 1 and 2 were produced. The steels were produced by melting them in a 100 kg vacuum melting furnace, assuming AOD production, which is an inexpensive process for producing stainless steel, and cast into slabs with a diameter of 180 mm. The steels were then produced into steel wires with a diameter of 5 mm under the following manufacturing conditions. In the following tables, values outside the range of the present invention are underlined.
[0055] The conditions are as follows. Specifically, the cast slab was heated at a heating temperature of 1200°C, rolled to a diameter of φ15mm at a processing temperature of 1050°C, and then annealed at an annealing temperature of 980°C for 50min. Then, cold drawing and annealing were repeated five times, followed by pickling and skin pass drawing. In this case, the final cold drawing rate was 31%, the heating rate during the final annealing was 90°C / min, the temperature during the final annealing was 980°C, the holding time during the final annealing was 50min, the cooling rate during the final annealing was 5°C / min, and the skin pass drawing rate was 10%.
[0056] [Table 1]
[0057] [Table 2]
[0058] The obtained steel wire rod was ND / / <110> The Fe2NbLaves phase fraction, the strength ratio of the Fe2NbLaves phase to Nb2CN, and the crack occurrence rate were measured. The results are summarized in Tables 3 and 4. These measurements were performed according to the following procedure.
[0059] ND / / <110> The fraction was calculated using the following formula by measuring a 500μm x 500μm area in one field of view at the surface layer, the center, and the 1 / 4 depth position between the surface layer and the center in the L cross section of the steel wire (a cross section parallel to the longitudinal direction of the steel wire and passing through the center line of the steel wire). The crystal orientation of each crystal grain was analyzed using FE-SEM / EBSD. The radial direction was defined as ND, and the crystal orientation in the ND direction was analyzed. <110> Display only the azimuth components within a clearance of 20°, and ND / / <110> The fraction was measured. Crystal orientation ND / / <110> Fraction = (Fraction (surface layer) x 2 + Fraction (1 / 4 depth position) x 2 + Fraction (center)) / 5
[0060] The intensity ratio of the Fe2Nb Laves phase to Nb2CN was determined by dissolving and extracting the precipitates from the entire cross section of the steel wire, and analyzing the precipitates collected from the extraction residue using XRD. In the diffraction chart, the maximum peak of Nb2CN is at 2θ = approximately 35°, and the maximum peak of the Fe2Nb Laves phase is at 2θ = approximately 44°. The intensity of these peaks with the background removed was measured, and the intensity ratio of the Fe2Nb Laves phase to Nb2CN was calculated.
[0061] The drop weight test was used to evaluate the resistance to cracking as follows. The test pieces were made into cylindrical shapes with a length of 15 mm, with the cross section of the steel wire being smoothed by cutting and milling. The test temperature was kept at -196°C using liquid nitrogen. The impact energy calculated by the following formula (1) was 20 J / cm 2 Ten test pieces were evaluated under the above conditions. Impact energy (J / cm 2 ) = mass of weight (kg) × acceleration of gravity (m / s 2 ) × Drop weight height (m) ÷ Test piece cross-sectional area in wire drawing direction (cm 2 ) · · · (1) Cracks were judged by visual inspection of the appearance after the test. The number of cracks per test piece was evaluated as the crack occurrence rate. If the crack occurrence rate was 80% or less, it was judged that the resistance to grain cracking was good.
[0062] [Table 3]
[0063] [Table 4]
[0064] Nos. 1 to 36 satisfied the requirements of the present invention and had good resistance to cracking, whereas Nos. 37 to 53 did not satisfy the requirements of the present invention and had poor resistance to cracking or poor corrosion resistance. EXAMPLES
[0065] Next, steel wires having various diameters were produced using φ15 annealed wire of steel type Q in Table 1 under the above-mentioned conditions, except that only the number of repeated cold wire drawing and annealing steps was changed. <110> The fraction, the strength ratio of the Fe2NbLaves phase to Nb2CN, and the crack occurrence rate were measured. The results are summarized in Table 5 below. As in Example 1, when the crack occurrence rate was 80% or less, it was determined that the resistance to chipping was good.
[0066] [Table 5]
[0067] Nos. 54 to 59 satisfied the requirements of the present invention and had good resistance to cracking. EXAMPLES
[0068] A steel wire having a diameter of 5 mm was produced using annealed wire of steel type Q shown in Table 1 under the conditions shown in Table 6. The produced steel wire was ND / / <110> The fraction, the strength ratio of the Fe2NbLaves phase to Nb2CN, and the crack occurrence rate were measured. The results are summarized in Table 6 below. As in Example 1 above, when the crack occurrence rate was 80% or less, it was determined that the resistance to chipping was good.
[0069] [Table 6]
[0070] Nos. 60 to 71 satisfied the requirements of the present invention and therefore exhibited good resistance to grain cracking, whereas Nos. 72 to 80 did not satisfy the preferred manufacturing conditions of the present invention and therefore exhibited poor resistance to grain cracking. [Industrial Applicability]
[0071] According to the present invention, a steel wire having excellent resistance to bending cracks can be obtained, and is extremely useful in industry.
Claims
1. In mass percent, C: 0.001-0.08%, Si: 0.01-3.0%, Mn: 0.01-2.0%, P: 0.20% or less, S: 0.050% or less, Ni: 0.01 to 4.0%, Cr: 8.0-30.0%, Mo: 0.01-4.0%, Cu: 0.01 to 3.0%, N: 0.001 to 0.10% and Nb: 0.2 to 2.0%; The steel has a composition including the remainder Fe and impurities, The radial crystal orientation ND / / <110> fraction is 0.12 or more, and Nb 2 Fe relative to the maximum peak of CN (2θ = about 35°) 2 A ferritic stainless steel wire having an intensity ratio of the maximum peak (2θ=approximately 44°) of the Nb Laves phase of 0.23 or less. Here, the radial crystal orientation ND / / <110> fraction means the area ratio of crystals in which the angle difference between the <110> orientation and the radial direction is 20° or less, and means a value calculated by the following formula using a 500 μm × 500 μm range in a single visual field measurement at the surface layer portion, the central portion, and the ¼ depth position portion between the surface layer portion and the central portion in an L cross section of the steel wire (a cross section parallel to the longitudinal direction of the steel wire and passing through the center line of the steel wire), and analyzing and evaluating the results as the fraction (surface layer portion), fraction (central portion), and fraction (¼ depth position portion), respectively. Crystal orientation ND / / <110> fraction = (fraction (surface layer) x 2 + fraction (1 / 4 depth position) x 2 + fraction (center)) / 5
2. The steel composition contains, in mass%, replacing a part of the Fe, Ti: 2.0% or less, V: 2.0% or less, B: 0.1% or less, Al: 4.0% or less, W: 2.5% or less, Ga: 0.05% or less, Co: 2.0% or less, Sn: 2.0% or less; 2. The ferritic stainless steel wire according to claim 1, further comprising one or more elements selected from the group consisting of Ta: 2.0% or less.
3. The steel composition contains, in mass%, replacing a part of the Fe, Ca: 0.05% or less, Mg: 0.012% or less, Zr: 0.012% or less; 3. The ferritic stainless steel wire according to claim 1, further comprising one or more selected from the group consisting of REM: 0.05% or less.
4. The ferritic stainless steel wire according to any one of claims 1 to 3, wherein a crack occurrence rate is 80% or less.
5. The cross-sectional shape of the steel wire is circular, The ferritic stainless steel wire according to any one of claims 1 to 4, wherein the circle has a diameter of 2 to 10 mm.
Citation Information
Patent Citations
High tensile strength steel having excellent weld heat affected zone toughness, and its production method
JP2005139509A
Ferritic stainless steel wire rod and steel wire, and method for producing them
JP2013147705A
Ferritic stainless linear steel material for fastening component
JP2017066431A
Rolled ferritic stainless-steel plate, process for producing same, and flange component
WO2015147211A1
Steel rod
WO2020196595A1